How difficult it was to acquire COVID digital certificate in summer 2021: Response of EU national contact points for cross-border health care. Issue 48 (July 2022) - Karacic, Jasna; Zanetti, Marco; Marusic, Ana
Highlights: Directive 2011/24/EU on patients' rights in cross-border healthcare shows important gaps. The Regulation on the EU Digital COVID Certificate raises a question about the strength of EU decisions that should be equal to all member states.